Home-based palliative care for caregivers of advanced cancer patients undergoing chemotherapy - Introntakun, kampon; Vittayatigonnasak, Arveewan; Arsanok, Pattamaporn; Silaguntsuti, Chureeporn; Thanasilp, Sureeporn (Vajira Nursing Journal, 2024)
Home-based palliative care for advanced cancer patients undergoing chemotherapy is essential, as it provides comfort in a familiar environment, reduces costs associated with hospital visits, and lowers the risk of infections related to chemotherapy. Nurses play a critical role in preparing caregivers by offering vital information, knowledge, and emotional support, helping to build their confidence and skills in managing symptoms and chemotherapy side effects. This support not only strengthens family relationships but also improves the patient’s quality of life. However, effective home-based palliative care requires an integrated approach, involving the family, healthcare systems, and community resources to enhance care quality and holistically address the patient’s needs.